Social support and social comparison tendencies predict trajectories of adolescents’ problematic social media use: A longitudinal study - Laura Salerno; Lucia Fortunato; Vivian Ostwald; Arianna Muscolino; Gianluca Lo Coco (PLoS ONE, 2025)
There is still no scientific consensus on the relationship between problematic social media use and its negative consequences for adolescents’ well-being. This study aims to identify common trajectories of problematic social media use over time in a sample of adolescents, and to identify the demographic and psychological factors associated with different empirical profiles. This four-wave longitudinal study involved 403 adolescents (age range: 13–18 years; Mage = 15.73 ± 1.22; 51.9% females). Participants provided demographic and social media use data (i.e., social media addiction, frequency of social media activities, time spent on Instagram and TikTok) as well as measures of psychological factors (i.e., psychological distress, emotion dysregulation, self-esteem, perceived social support, online social comparison). Parallel latent class growth analysis (LCGA) categorised participants into three classes. Participants in class 1 (‘most vulnerable group’; 25.56%) showed a more impaired functioning profile, with a stable problematic pattern of social media use (i.e., high levels of social media addiction and time spent on TikTok). Multinomial regression models showed that factors associated with this pattern were low social support, high online social comparison, and SMU intensity. Our findings suggest that the role of social interactions (both online and offline) and social comparison tendencies should be further explored as markers of problematic social media use.